Tropical dermatology: Marine and aquatic dermatology - Haddad, Vidal [UNESP]; Lupi, Omar; Lonza, Juan Pedro; Tyring, Stephen K. (Mosby-elsevier, 2009)
Dermatoses caused by marine organisms are frequently seen in dermatology clinics worldwide. Cutaneous injuries after exposure to marine environments include bacterial and fungal infections and lesions caused by aquatic plants and protists. Some of these diseases are well known by dermatologists, such as Vibrio vulnificus septicemia and erysipeloid, but others are uncommon, such as envenomation caused by ingestion or contact with certain dinoflagellates or cyanobacteria, which are associated with rashes that can begin Within minutes after exposure. Many marine/aquatic invertebrates, such as sponges, cnidarians, echinoderms, crustaceans, and mollusks, are associated with different kinds of dermatologic lesions that call vary from irritant or allergic contact dermatitis to physical trauma and envenomations. These cutaneous lesions May result in mild local reactions or can be associated with severe systemic reactions. Invertebrate animals, such as cnidarians, sea urchins, and worms, and aquatic vertebrates, such as venomous fishes and stingrays, are commonly associated with skin lesions in many countries, where they call constitute occupational dermatoses among fishermen and scuba divers, but they can also be observed among persons who contact these animals in kitchens or beaches. The presence of unusual lesions, a recent travel history, and/or a report of contact with an aquatic environment (including ownership of a marine or freshwater aquarium) should alert the dermatologist to the etiology of the cutaneous problems. (J Am Acad Dermatol 2009;61:733-50.)
Keywords: cnidarians; contact dermatitis; crustaceans; envenomation; fish; mollusks